Follicular Output Rate and Follicle-to-Oocyte Index of Low Prognosis Patients According to POSEIDON Criteria: A Retrospective Cohort Study of 32,128 Treatment Cycles - Chen, Lijuan; Wang, Hui; Zhou, Hanying; Bai, Haiyan; Wang, Tao; Shi, Wenhao; Shi, Juanzi (Frontiers in Endocrinology, 2020)
Objective To investigate ovarian sensitivity in subgroups of patients with a low prognosis, as defined by the POSEIDON criteria, undergoing in vitro fertilization treatment and measures to improve ovarian sensitivity in these patients. Design We conducted a retrospective cohort analysis. Setting The study was conducted at an IVF clinic in a public hospital. Patients A total of 32,128 fresh IVF cycles from January 2014 to October 2018 at a single IVF clinic were included in the analysis. Patients with a low prognosis were categorized into four groups based on the POSEIDON criteria. Interventions None. Main Outcome Measure The primary outcome measures were the follicular output rate (FORT) and the follicle-to-oocyte index (FOI). Results The FORTs in the order from the highest to the lowest were 1.18 in group 3, 0.98 in group 4, 0.76 in group 1, and 0.68 in group 2. The trend in the FOI values was consistent with that in the FORTs. Among patients with poor ovarian sensitivity, 58.41% of patients with FORTs ≥ 0.30 in the second cycle underwent an adjustment to the ovarian stimulation (OS) protocol and 41.59% underwent an adjustment to the gonadotropin (Gn) starting dose. Among patients with normal ovarian sensitivity, 43.56% of those with FORTs ≥ 0.80 in the second cycle underwent an adjustment to the OS protocol and 56.44% underwent an adjustment to the Gn starting dose. Conclusion Ovarian sensitivity was the highest in group 3 (young women with poor ovarian reserve), followed by groups 4 (women at advanced age with poor ovarian reserve) and 1 (young women with good ovarian reserve), and it was the lowest in group 2 (women at advanced age with good ovarian reserve). For patients with poor ovarian sensitivity, it is preferred to recommend an adjustment to the OS protocol, while for those with normal ovarian sensitivity, adjusting the Gn starting dose is preferred.